2011
DOI: 10.1021/nn202510n
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Nanostructures of Antigen Provide an Effective Means for Regulating Mast Cell Activation

Abstract: Nanostructures containing 2,4-Dinitrophenyl (DNP) as antigen were designed and produced to investigate antibody-mediated activation of mast cells. The design consists of nanogrids of DNP termini inlaid in alkanethiol self-assembled monolayers (SAMs). Using scanning probe-based nanografting, nanometer precision was attained for designed geometry, size and periodicity. Rat basophilic leukemia (RBL) cells exhibited high sensitivity to the geometry and local environment of DNP presented on these nanostructures. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 62 publications
(150 reference statements)
1
47
0
Order By: Relevance
“…16 This spatial arrangement brings Fc ε RI and Lyn into proximity. Lyn plays a positive role in this signaling pathway, 40 leading to phosphorylation of tyrosine residues within ITAMs in Fc ε RI.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…16 This spatial arrangement brings Fc ε RI and Lyn into proximity. Lyn plays a positive role in this signaling pathway, 40 leading to phosphorylation of tyrosine residues within ITAMs in Fc ε RI.…”
Section: Resultsmentioning
confidence: 98%
“…17,18,42,43 Our prior work revealed that surface-bound antigens, when positioned at a matching geometry of closely packed Fc ε RI protein molecules, exhibit high potency in activating mast cells. 16 This evidence, collectively, suggests that the presentation of the antigen or hapten at the nanometer level dictates the arrangement of cellular receptors and thus impacts signaling pathways. Specifically, clustering (in 20 nm periodicity) of antigen such as DNP hepten is known to activate antibody-Fc ε RI-mediated activation among mast cells, while lack of or significant reduction of clustering hampers the activation signaling cascades.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations